Improved HDAC Inhibition, Stronger Cytotoxic Effect and Higher Selectivity against Leukemias and Lymphomas of Novel, Tricyclic Vorinostat Analogues - Bartosz Bieszczad; Damian Garbicz; Marta Świtalska; Marta K. Dudek; Dawid Warszycki; Joanna Wietrzyk; Elżbieta Grzesiuk; Adam Mieczkowski (MDPI AG, 2021)
Histone deacetylase (HDAC) inhibitors are a class of drugs used in the cancer treatment. Here, we developed a library of 19 analogues of Vorinostat, an HDAC inhibitor used in lymphomas treatment. In Vorinostat, we replaced the hydrophobic phenyl group with various tricyclic 'caps' possessing a central, eight-membered, heterocyclic ring, and investigated the HDAC activity and cytotoxic effect on the cancer and normal cell lines. We found that 3 out of the 19 compounds, based on dibenzo[b,f]azocin-6(5H)-one, 11,12-dihydrodibenzo[b,f]azocin-6(5H)-one, and benzo[b]naphtho[2,3-f][1,5]diazocine-6,14(5H,13H)-dione scaffolds, showed better HDACs inhibition than the referenced Vorinostat. In leukemic cell line MV4-11 and in the lymphoma cell line Daudi, three compounds showed lower IC50 values than Vorinostat. These compounds had higher activity and selectivity against MV4-11 and Daudi cell lines than reference Vorinostat. We also observed a strong correlation between HDACs inhibition and the cytotoxic effect. Cell lines derived from solid tumours: A549 (lung carcinoma) and MCF-7 (breast adenocarcinoma) as well as reference BALB/3T3 (normal murine fibroblasts) were less susceptible to compounds tested. Developed derivatives show improved properties than Vorinostat, thus they could be considered as possible agents for leukemia and lymphoma treatment.